Effect of Endophytic bacteria on growth and suppression of ganoderma infection in oil palm. - Sapak, Zaiton; Meon, Sariah; Mior Ahmad , Zainal Abidin (Friends Science Publishers, 2008)
Basal stem rot (BSR) caused by Ganoderma boninense is an important disease of oil palm in Malaysia. Control of BSR is complex, because the disease occurs in the dynamic environment at the interface of the roots with soil. Endophytes as biocontrol agents offer possible advantages as they invade and proliferate in the plants to await the pathogens and they are insulated from any adverse conditions in the soil. Burkholderia cepacia (B3) and Pseudomonas aeruginosa (P3) isolated from symptomless oil palm root tissues have shown potential to inhibit the spread of G. boninense. They play a role in keeping the G. boninense population below threshold for BSR initiation by restricting its entry and movement in the palm. When tested on 4 month-old oil palm seedlings inoculated with G. boninense, the bacteria singly and in a mixture suppressed the spread of the pathogen with an epidemic rate of 0.10 - 0.24 units compared to 0.52 units in the control. At 8 months after inoculation, BSR incidence was reduced by 76% in seedlings pre-inoculated with P. aeruginosa (P3). B. cepacia (B3) reduced incidence by 42% and the mixture of P. aeruginosa and B. cepacia by 54%. Inoculation of endophytic bacteria also improved vegetative growth of oil palm seedlings.